2016
DOI: 10.4236/ajps.2016.76076
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Determination of Effective Diffusivity of Mesquite during Convective Drying

Abstract: The mesquite pods have a high nutritional value, being a rich source of sugars, proteins, minerals and fibers that can be used as a raw material for the development of a number of food products and technological innovations. The objective of this work was to study the drying kinetics of mesquite pods in a thin layer, 20 mm length and determine the effective diffusion coefficient by adjusting mathematical models that were based on heat transfer and mass fundamentals. For the experiments, we used mature mesquite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These authors state that one of the main challenges of adding any legume to a bakery product is the rheological changes in the dough and the final product. Pereira de Gusmão et al [30,31], quoting González-Montemayora et al [20], concluded that the use of flour from Neltuma fruits with a size between 500 and 100 μm is suitable for products such as bread, cakes and cookies. The rheology, tenacity and extensibility of the dough decreases as the concentration of "algarrobo" flour increases and the more quantity is added, the weaker the remaining dough.…”
Section: Neltuma ("Algarrobo") Flourmentioning
confidence: 99%
“…These authors state that one of the main challenges of adding any legume to a bakery product is the rheological changes in the dough and the final product. Pereira de Gusmão et al [30,31], quoting González-Montemayora et al [20], concluded that the use of flour from Neltuma fruits with a size between 500 and 100 μm is suitable for products such as bread, cakes and cookies. The rheology, tenacity and extensibility of the dough decreases as the concentration of "algarrobo" flour increases and the more quantity is added, the weaker the remaining dough.…”
Section: Neltuma ("Algarrobo") Flourmentioning
confidence: 99%
“…Henderson et al [39,40] used the thin layer approach and derived the analytical solution given in Eq. ( 18).…”
Section: Dryingmentioning
confidence: 99%
“…a, b, c, m, n: model coefficients, dimensionless; k: drying constant, min -1 ; t: drying time, min. Source: Leite (2019), Gusmão (2016).…”
Section: (4)mentioning
confidence: 99%